THE INVESTIGATION AUTHORITY OF CRIMINAL ACTION MONEY LAUNDERING (AML) FOR JUSTISIABLE OF MILITARY JUSTICE - IRMAN PUTRA; ARIEF FAHMI LUBIS (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Investigators of predicate crimes who are authorized to conduct ML investigations have determined in a limited manner, namely only appointing investigators from the State Police agency Republic of Indonesia, Attorney General's Office, Corruption Eradication Commission (KPK), National Narcotics Agency (BNN) and the Directorate General of Taxes and the Directorate of Customs and Excise of the Ministry of Finance Republic of Indonesia, meanwhile a TNI soldier, TNI Investigator is not on the list as an investigator for predicate crimes. The purpose of this study is to analyze the authority TNI investigators in conducting an investigation of money laundering offenses allegedly committed by Justisiabel Military Courts are still a problem, on the other hand there should be no omission of every act that violates the law in the pursuit of justice and legal certainty. Method The approach used in this research is a sociological juridical approach with using secondary data and reinforced by primary data. Secondary data obtained from interviews with resource persons, and questionnaires distributed to nurses in the District Sidoarjo, while secondary data were obtained from the statute approach and conceptual approach. The sampling method chosen is the purposive sampling method which is considered to be able to represent the population. The data obtained from this study were then analyzed qualitatively to answer the problems in this research. The results of this study indicate that according to the applicable procedural law within the Military Courts which are authorized to conduct an investigation into a criminal act allegedly committed by a Judicial Justicia he military is a TNI Investigator, it turns out that it can't be applied immediately in the process ML investigation because the Law (UU TPPU) has determined otherwise, in providing ML investigation authority.